Drivers of the North Aegean Sea Ecosystem (Eastern Mediterranean) Through Time: Insights From Multidecadal Retrospective Analysis and Future Simulations - Tsagarakis, Konstantinos; Libralato, Simone; Giannoulaki, Marianna; Touloumis, Konstantinos; Somarakis, Stylianos; Machias, Athanassios; Frangoulis, Constantin; Papantoniou, Georgia; Kavadas, Stefanos; Stoumboudi, Maria Th. (Frontiers in Marine Science, 2022)
Ecosystem models are important tools for the implementation of Ecosystem Based Fisheries Management (EBFM), especially in highly exploited ecosystems affected by climate change, such as the Mediterranean Sea. Herein, we present the development of an Ecopath ecosystem model for the North Aegean Sea (Eastern Mediterranean) in the early 1990s, as well as the parameterization of the temporal dynamic module (Ecosim) after fitting to catch and relative biomass time series for the period 1993-2020. The Ecosim model included as drivers (i) fishing, assuming a technology creep factor of 2% annual increase (0.79% for bottom trawls), (ii) Sea Surface Temperature, (iii) trophic interactions and (iv) a Primary Production (PP) Anomaly which was positively correlated with the North Atlantic Oscillation of the previous year, highlighting the synergistic effect of environmental and anthropogenic processes during the three-decades hindcast period. Trends in biomasses, catches and ecosystem indicators were characterized by a decline from 1993 to 2010 and a strong recovery thereafter. Sea warming scenarios for the period 2021-2050 indicated contrasting responses to increased temperature among the main commercial groups, while simulations of changes in productivity had relatively straightforward effects. Two scenarios of 10% and 25% reduction in fishing effort revealed quick increases in the biomass of most commercial species, though coupled with lower catches due to reduced fishing, except for few groups that their population increase was remarkably high. Although the 25% effort reduction resulted in high recoveries in the short term, it didn’t necessarily lead to constantly high biomasses resulting in reduced catches towards the end of the forecast period for some groups, in contrast to the 10% reduction. When impacts of reduced productivity were added to temperature effects, the model forecasted lower biomass increases for the winners of sea warming and even higher decreases for the losers. Biomass losses were compensated by a 10% reduction in fishing effort, but this was not overall enough to counterbalance losses in catches. The model developed here contributes to better elucidate observed changes in the past and to hind directions of change in future simulations, as well as to advance EBFM in the area.